Security Pattern of Correctional Institution Against Narcotics Prisoners (A Case Study at Class IIA Correctional Institution Pekanbaru): POLA PENGAMANAN LEMBAGA PEMASYARAKATAN II A PEKANBARU - Harles Marbun, Putra Andreas Marbun; Kasmanto Rinaldi, (Sisi Lain Realita, 2025)
Narcotics inmates require special attention in the rehabilitation process, one of which is through observation patterns carried out by correctional officers. This study aims to describe the security pattern implemented by the Class IIA Pekanbaru Prison for narcotics inmates and identify supporting and inhibiting factors in its implementation. The method used is a qualitative approach with a descriptive research type. The results show that the security pattern is implemented continuously through direct observation of inmate behavior, regular reporting, and evaluation of developments in the rehabilitation program. This pattern aims to assess the mental readiness, behavior, and attitudes of inmates in participating in the social reintegration program. Supporting factors include cooperation between officers and the existence of a structured correctional administration system, while obstacles are the limited number of officers and the high number of inmates. In conclusion, the security pattern implemented at the Class IIA Pekanbaru Prison plays an important role in supporting the success of the security process for inmates, especially narcotics.